Investigating the effect of brand personality on customers' loyalty with moderating role of customers' commitment (case study: Tuka Transportation Co. (PLC), Esfahan, Iran). (2016) - Hosseini, Seyed Hasan; Mashkani, Abolfazl Jannati; Hashemi, Mohammad Mahdi Sadr; Abdellahi, Sayed Amin
This study is chiefly concerned with examining the likely associations between the variables brand personality, customer commitment, and customer loyalty in Tuka Company (PLC) from Iran's transportation industry. Based on the assumed relationships in the research model, the required data was collected from the questionnaire distributed among customers. To examine the likely associations between variables and for test of the hypotheses, multiple regression and structural equation modelling (path analysis) were performed. The results indicated that at a 95% confidence interval there was a positive and significant relationship between brand personality and customer commitment. Brand personality was also found to be positively and significantly associated with customer loyalty. In addition, customer commitment had a positive and significant relationship with customer loyalty. And lastly, the results supported significant effect of customer commitment on the relationship of brand personality with customer loyalty.